A fully atomistic model of the Cx32 connexon. - Sergio Pantano; Francesco Zonta; Fabio Mammano (PLoS ONE)
Connexins are plasma membrane proteins that associate in hexameric complexes to form channels named connexons. Two connexons in neighboring cells may dock to form a "gap junction" channel, i.e. an intercellular conduit that permits the direct exchange of solutes between the cytoplasm of adjacent cells and thus mediate cell-cell ion and metabolic signaling. The lack of high resolution data for connexon structures has hampered so far the study of the structure-function relationships that link molecular effects of disease-causing mutations with their observed phenotypes. Here we present a combination of modeling techniques and molecular dynamics (MD) to infer side chain positions starting from low resolution structures containing only C alpha atoms. We validated this procedure on the structure of the KcsA potassium channel, which is solved at atomic resolution. We then produced a fully atomistic model of a homotypic Cx32 connexon starting from a published model of the C alpha carbons arrangement for the connexin transmembrane helices, to which we added extracellular and cytoplasmic loops. To achieve structural relaxation within a realistic environment, we used MD simulations inserted in an explicit solvent-membrane context and we subsequently checked predictions of putative side chain positions and interactions in the Cx32 connexon against a vast body of experimental reports. Our results provide new mechanistic insights into the effects of numerous spontaneous mutations and their implication in connexin-related pathologies. This model constitutes a step forward towards a structurally detailed description of the gap junction architecture and provides a structural platform to plan new biochemical and biophysical experiments aimed at elucidating the structure of connexin channels and hemichannels.